Autoestima, estrategias de afrontamiento asociados al estrés académico en estudiantes de enfermería – UNT en tiempos COVID-19 - Arenas Castro, Vanesa Maribel (2021)
The present quantitative, descriptive correlational, cross-sectional research aimed to determine the association that exists between the level of self-esteem, coping styles and the level of academic stress of nursing students – UNT in times of Covid-19. The sample universe consisted of 133 nursing students who met the inclusion criteria; Three instruments were used for data collection: Coopersmith Adult Self-Esteem Scale; Barraza Academic Stress Assessment Scale and Carver's Stress Coping Modes Questionnaire (COPE). To measure the association between variables, Kendall's Tau b and c test was used. The results were: 45.9 percent obtained high self-esteem level, 39.1 percent, medium level and 15.0 percent, low level. In relation to Coping styles, 56.4 percent their style was focused on emotions, 30.1 percent focused on the problem, 12.0 percent two or more styles and 1.5 percent other coping styles and according to stress level, 63.5 percent presented medium stress level, 20.3 percent low level and 16.3 percent high level. It is concluded that there is a negative and inverse relationship between level of self-esteem and level of stress (Tau-b Kendall: -0.397 p=0.00), on the contrary, there is no relationship between coping strategies and stress level (p=0.372).